(untitled) (Brazilian Journal of Radiation Sciences, 2021)
NORM minerals generate, after metallurgical processing, radioactive slags that can be controlled by CNEN. Thus, it is necessary to establish a reprocessing route to make the material exemption. The route necessarily passes through the characterization of the slag from its physical properties. In this paper the results of the variation of the concentrations of U and Th oxides with the electrical, and magnetic properties of the slag, with their granulometry and with their density are presented. It has been observed that the metallurgical processing produces as slag a slag with molecular connections between the oxides that constitute it. In this way, the separation of the oxides will only be possible with the leaching of the slag.